The Value of Eucalypts in Asia - Thirawat, Sukhum (Indian Forester, 1956)
With nearly one-third of the World area, Asia has 13.7 per cent of World forests, and the lowest per capita forest area. Subsisting on a current import of 2 million M3. of timber yearly, Asia is producing ,6 million more habitants each year. The forest situation is thus acute, since the productivity of the existing forests is also among the lowest due to the profuse mixture of plants, economic or otherwise. One of the most effective means of remedying the situation is by establishing fast-growing and high-yield plantations, so as to catch up with the exploitation, and thus operate on a sustained yield basis, as already effected in U.S.A. The Eucalypts have admirable attributes in their phenomenal growth and great adaptability: thus their judicious use should materially help to achieve the above objective. Asia’s past uses of the Eucalypts are very insignificant compared with other regions. The leading country, India, very early and enthusiastically experimented with about 100 species and after sometime lost interest, thus adversely affecting the thoughts in neighbouring countries. The only success at present is with E. globulus for firewood on the Nilgiris hills with only 1,800 acres. In the light of the current experiences, while no dogmatic rules regarding acclamatisation can be entertained, the author proposes criteria for the judicious selection of species based on the natural habitat and requirements of the species. Specific suggestions for the various climatic zones are also offered, drawing largely from the 1952 F.A.O. Eucalyptus Study Tour in Australia. It is proposed also that objectives should be reoriented on a rational basis. For the average country a short rotation up to 30 years should be aimed at for provision of firewood, sleepers, poles and posts, rather than timber. The Eucalypts could very well provide a much better quality of such products in less time than the indigenous species. The author also proposes a definite system for carrying out acclamatisation trials, including also nursery practices, based on practical experience in Tropical Asia.